Misfits of War: First World War Nurses in the Daughters of Mars by Thomas Keneally - Branach-Kallas, Anna (Studia Anglica Posnaniensia, 2017)
The article is an analysis of the representation of Australian nurses in Thomas Keneally 2012 First World War novel, The Daughters of Mars. Inspired by rigorous research, Keneally fictionalizes the lives of two nursing sisters in the Middle East, on a hospital ship in the Dardanelles, as well as in hospitals and casualty clearing stations on the Western Front. His novel thus reclaims an important facet of the medical history of the First World War. The author of the article situates her analysis in the context of historical research on the First World War and the Australian Anzac myth, illuminating the specifically Australian elements in Keneally’s portrait of the Durance sisters. She demonstrates that The Daughters of Mars celebrates the achievements of “Anzac girls”, negotiating a place for them in the culture of commemoration. Yet, at the same time, Keneally attempts to include his female protagonists in the “manly” world of Anzac values, privileging heroism over victimization. Consequently, they become “misfits of war”, eagerly accepting imperial and nationalist ideologies. Thus, in a way characteristic of Australian First World War literature, The Daughters of Mars fuses the tropes of affirmation and desolation.